Molecular Epidemiology of Genogroup II Noroviruses Infection in Outpatients with Acute Gastroenteritis in Nanjing, China (2010–2013). (15th July 2014) - Hong-ying, Zhang; Li-min, Shi; Wei, Li; Xuan, Wang; Meng-kai, Qiao; Min, He; Yan, Wang; Guo-xiang, Xie
Abstract : Objective. Human noroviruses (NoVs) of genogroup II are the most common strains detected in sporadic cases of acute nonbacterial gastroenteritis in outpatients in Nanjing. To gain insight into the molecular epidemiology of GII strains, we analyzed 75 positive NoV cases from 2010 to 2013. Methods. The sporadic cases were detected by real-time PCR with specific primers and probes to human NoVs of genogroup I or II, human sapovirus, human rotavirus, human astrovirus, and human enteric adenovirus. Human NoVs of genogroup II were further studied by VP1 amplification (RT- PCR), cloning, sequencing, and phylogenetic analysis. Results. Rotavirus and human NoVs were more frequently detected in all the cases from 2010 to 2013. Human NoVs infection was more frequent since 2011 and more frequent than rotavirus infection after 2012. Out of the 75 NoV cases of genogroup II, there were 5 GII.6, 11 GII.3, and 59 GII.4. Of the 59 GII.4, 27 cases were previous GII.4.2006b strains that circulated between 2010 and 2012; while 32 cases were the newly emerging GII.4 strains GII.4.2012 from 2011 to 2013. Conclusion. Our data confirm other studies on the rapid emergence and displacement of highly virulent GII.4 strains.